Exploring the Reading Strategies of Performing Humanities and Social Sciences of Senior High School Students - Bon Christian Lloyd Comique; Justine Joy Rojo; Angel Shane Suan; Aris Pet Angeli Suarez; Genesis Naparan (Journal of Elementary and Secondary School, 2025)
This study explores the reading strategies employed by performing Humanities and Social Sciences (HUMSS) students. It examines their reading material preferences, reading motivations, reading strategies, challenges encountered, and coping strategies developed. The research acknowledges the potential of reading materials to enhance academic development and gain confidence, belonging, and knowledge acquisition. However, it also recognizes that motivational factors can be accompanied by challenges such as difficulty concentrating and procrastination. A Qualitative Merriam Case Study method was used to investigate the reading strategies of 15 performing HUMSS students, supplemented by interviews with 2 peers for triangulation. Data collected from these interviews were analyzed and categorized to identify recurring themes and patterns. The findings reveal that performing HUMSS students are motivated by both internal and external rewards, information prioritization, and peer influence. These students face challenges such as difficulty in concentration, reading, and procrastination. To address these challenges, they employ self-guided or independent reading strategies and collaborative strategies. The study concludes that performing HUMSS students demonstrate flexibility and adaptability in their reading approaches, adjusting their strategies to overcome challenges. This suggests that a combination of independent and collaborative techniques is effective in maintaining reading engagement and comprehension among students.